2016
DOI: 10.3329/jbas.v40i1.28324
|View full text |Cite
|
Sign up to set email alerts
|

Natural Radioactivity and dose Assessment in Sand and Sediment Samples from Kuakata Beach, Bangladesh

Abstract: . The estimated outdoor annual effective dose varied between 0.22 and 1.79 mSv/year with a mean value of 0.55 mSv/year, which is higher than the world average for outdoor annual effective dose (0.07 mSv/year). The external hazard indices for the samples varied from 0.17 to 1.43 with the average value of 0.44, which is less than the unity. The average value of radium equivalent activity was estimated and found to be 161.40 BqKg -1 which is less than the acceptable limit of world average value of 370 BqKg -1 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…The obtained means concentrations of 40 K, 238 U and 232 Th in the study area exceeded both the values of the control and world standard limit of 400 Bqkg −1 , 35 Bqkg −1 and 30 Bqkg −1 respectively [ 38 ]. Similarly, the concentrations of 40 K, 238 U and 232 Th in the present study was found higher than those reported elsewhere around the world [ [4] , [5] , [6] , [22] , [24] , [25] , [26] , [37] , [39] , [40] , [41] , [42] ] but compared favorably with results reported by Refs. [ 43 , 44 ].…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The obtained means concentrations of 40 K, 238 U and 232 Th in the study area exceeded both the values of the control and world standard limit of 400 Bqkg −1 , 35 Bqkg −1 and 30 Bqkg −1 respectively [ 38 ]. Similarly, the concentrations of 40 K, 238 U and 232 Th in the present study was found higher than those reported elsewhere around the world [ [4] , [5] , [6] , [22] , [24] , [25] , [26] , [37] , [39] , [40] , [41] , [42] ] but compared favorably with results reported by Refs. [ 43 , 44 ].…”
Section: Resultssupporting
confidence: 81%
“…where H Ra , H Th and H K are the activity concentrations of 40 K, 238 U and 232 Th, respectively in Bqkg −1 [ [6] , [15] , [37] , [46] , [47] ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Ahmed et al (2016) investigated the levels of natural radioactivity in sand and soil samples collected from Kuakata Beach, Bangladesh. The samples were analyzed for radionuclides using a gamma spectrometry system equipped with a p-type coaxial HPGe detector.…”
Section: Findings Of Earlier Studies and Discussionmentioning
confidence: 99%